Digital Literacy In Detecting Hoaxes In Instagram Media (Analysis Study Of Communication Science Students, State Islamic University Of North Sumatra) - Ulfa, Azzahra; Sikumbang, Ahmad Tamrin (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Abstract This article explores the urgency of digital literacy in detecting hoaxes on social media, especially Instagram, among students of Communication Sciences of the State Islamic University of North Sumatra (UINSU). This research identifies crucial problems in the spread of false information or hoaxes that have the potential to divide society and damage information integrity. This study uses a qualitative methodology, this research adopts an ethnographic approach and a constructive paradigm to gain a deep understanding of how students perceive and respond to the information they find on social media. The location of this study is Campus 4 Tuntungan UINSU, and the resource persons were selected through purposive sampling based on their experience and activeness in using Instagram as well as their involvement in digital literacy issues. Primary data sources are obtained from in-depth interviews and participatory observations, while secondary data sources include relevant document studies. The data analysis technique used is the Miles, Huberman, and Saldana analytical model which includes data reduction, data presentation, and conclusion drawn. The validity test of the data was carried out through source triangulation. The results of the study show that even though students have access to digital literacy tools, there is still a tendency to trust and spread unverified content. The conclusion of the study emphasizes that digital literacy is not only important as a tool to verify information and avoid the spread of hoaxes, but also as a means to increase critical awareness of media content.